Estudio de prefactibilidad para la instalación de una planta productora de licor a base de higo fermentado para el mercado local - Véliz Rueda, Víctor Oscar (2016)
The theme of this project is the installation of a fig liqueur plant for the Lima market, this product is intended to be considered as a new option for consumption of alcoholic drinks, it can be drunk at all times, mainly as accompaniment in foods.